Laparoscopic versus opengastric surgery for the treatment of pathological T1N0M0 gastric cancer in elderly patients: a matched study - Haiyan Pan (Nature Portfolio, 2017)
Abstract The aim of this study was to compare the outcomes of laparoscopic surgery (LAP) and open gastric surgery (OP) in early gastric cancer patients aged ≥70 years.We conducted a retrospectively analysis among patientswith pathological T1N0M0 gastric cancer,who underwent LAP or OP between January 1, 2001 and December 31, 2008. We identified a well-balanced cohort of 2,360 patients (1180 patients in each group). LAP has been shown to offer a superior perioperative results to OP, including lower blood loss, shorter time to oral intake, walk and bowel function recovery, shorter time of hospital stay, and less blood transfusion required. However, the intraoperative and postoperative complications, local recurrence, and metastasis didn’t show statistically significant differences between groups. The 5-year overall survival (OS), disease-free survival (DFS), and cancer-specific survival (CSS) were 60.1% vs.63.2%, 80.8% vs. 83.3%, and 87.6% vs. 89.5% in the LAP group and OP group, respectively. The hazard ratios (HR) for OS, DFS, and CSS were 1.09(95% confidence interval [CI]: 0.95–1.25; P = 0.215), 1.03(95% CI: 0.91–1.18; P = 0.636), and 1.07 (95% CI: 0.88–1.30; P = 0.484), respectively, compared LAP group with OP group. In conclusion, LAP is an acceptable alternative to OP in elderly patients with early gastric cancer.